PELATIHAN PEMANFAATAN CLOUD COMPUTING DALAM PENYIMPANAN FILE BAGI GURU-GURU UPTD SDN. 014671 SENTANG - Masitah Handayani; Fauriatun Helmiah; Riki Andri Yusda; Abdul Azis Ubaidillah (Smart Education, 2023)
Abstract: The development of science and technology in the current global era plays an important role in all sectors, one of which is in the field of education. Currently, many new breakthroughs are emerging that keep up with the times, for example Cloud Compting. Cloud computing is an information system that allows easy access to resource components such as servers, applications and databases via the internet network. By using this system, resources will be stored and managed in a data center connected to the internet.Cloud Computing has many roles in the world of education. Utilizing cloud computing can save costs and prevent the implementation of complicated technology. One form of use of cloud computing in the world of education is in file (data) storage. The result of this activity is the achievement of the goal by observing and continuing to monitor the teachers that the teachers have successfully used cloud computing in storing data via cloud computing and have not experienced any difficulties. Keywords: cloud computing; file; teacher Abstrak: Perkembangan IPTEK di era global pada saat ini sangat berperan penting dalam segala sektor, salah satunya adalah dalam bidang pendidikan. Pada saat ini, banyak bermunculan terobosan baru yang mengikuti perkembangan zaman, misalnya Cloud Computing. Cloud computing merupakan sebuah sistem informasi yang memungkinkan kemudahan akses kepada komponen sumber daya seperti server, aplikasi, dan database melalui jaringan internet. Dengan menggunakan sistem ini, sumber daya akan disimpan dan dikelola di pusat data yang terhubung dengan internet. Cloud Computing memiliki banyak peran dalam dunia pendidikan. Pemanfaatan cloud computing ini dapat menghemat biaya dan mencegah terjadinya penerapan teknologi yang rumit. Salah satu bentuk pemanfaatan cloud computing dalam dunia pendidikan adalah dalam penyimpanan file (data). Hasil dari kegiatan ini adalah tercapainya tujuan dengan melihat dan terus melakukan pemantauan terhadap para guru bahwa guru telah berhasil menggunakan cloud computing dalam penyimpanan data melalui cloud computing dan tidak mengalami kesulitan. Kata Kunci: cloud computing; file; guru